Trends in Neurosurgical Treatment for Chronic Subdural Hematoma in Germany: A National Survey - Mertens, Robert; Kersting, Katharina; Shaked, Zoe; Truckenmüller, Peter; Früh, Anton; Vajkoczy, Peter; Wessels, Lars (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Background Chronic subdural hematoma (cSDH) is a common neurosurgical condition of growing importance due to the aging population and increasing use of antithrombotic agents. Due to the lack of guidelines, great variability is observed in the treatment of cSDH. We conducted a multicenter, nationwide survey to assess the differences in treatment across Germany in the context of surgical practices discussed in the literature.Methods A web-based survey was designed using the REDCap electronic data capture tool hosted at the Charité – Universitätsmedizin Berlin. The survey was divided into four parts: preoperative management and indication for surgery, perioperative management of medication, surgical technique, and postoperative management. The survey was distributed to German neurosurgical departments through the newsletter of the German Society of Neurosurgery and direct e-mail contact and could be answered by one member of each department between March 1 and May 31, 2023.Results Overall, representatives of 46 German neurosurgical departments completed the survey. Participants needed a mean time of 16:25 minutes (standard deviation [SD] ± 27:47 minutes) to complete the survey. The mean caseload of the participating departments was 1,831.5 (range: 300–6,000; SD ± 1,130.7) operations per year, including 87.8 procedures for cSDH (range: 15–300; SD ± 73.6). Evidence found in the literature regarding the performance of a burr hole craniotomy, use of a drain, passive drainage, removal of the drain 48 hours after surgery, and early mobilization after surgery was consistently implemented in the management of the surveyed departments. On the contrary, recommendations regarding the performance of surgery under local anesthesia, use of subgaleal drains, postoperative Valsalva maneuvers, and avoidance of postoperative computed tomography (CT) if possible were not universally implemented.Conclusion This survey indicates that there is no consensus on the treatment of cSDH in Germany and that the steadily increasing evidence from clinical trials must be implemented in national and international guidelines. The development of tailored treatment strategies for older patients with multiple risk factors and comorbidities is of particular importance.
Keywords: cSDH; survey; burr hole craniotomy; antiplatelet drugs; anticoagulants